Inventory Level Analysis of Horticultural Commodities Exported by PT BSL from Central Java Indonesia to Singapore - Nashih, AM Sa’dun; Widodo, Kuncoro Harto; Ismoyowati, Dyah (KnE Life Sciences, 2016)
Horticultural commodities, in Indonesia, are one of the main clusters of export commodities. The demand of the commodities is relatively high due to the high economic level of consumers in Singapore. The exporter, e.g., PT BSL, had difficulties to meet the demand of Singapore’s importer. This problem will be analyzed with inventory system in the supply chain of vegetables and fruits exported from Central Java Indonesia to Singapore. To identify the problem, we combine a dynamic system approach and its validation. The data on existing conditions (with the level of rejection = 20%) were then formulated and modeled with two alternative scenarios, scenario1 and 2. In scenario 1, the level of rejection was set at the level of 10%, while scenario2 at the level of 30%. Based on the simulation results, it was found that the average level of inventory in the scenario 1 was at 661.9 kg per day, while in scenario 2 were 112.34 kg per day. Keywords: dynamic systems, horticultural commodities, inventory, supply chain